2017
DOI: 10.1002/hon.2378
|View full text |Cite|
|
Sign up to set email alerts
|

Refractoriness to immunochemotherapy in follicular lymphoma: Predictive factors and outcome

Abstract: Follicular lymphoma is characterized by a good response to immunochemotherapy (ICT). However, a small percentage of patients responds poorly to treatment and seems to have a worse outcome. This study attempted to identify the predictive factors and outcome of refractoriness to first-line ICT. All patients diagnosed with stage II to IV follicular lymphoma between 2002 and 2014 and treated with first-line ICT in 4 Spanish institutions were analyzed. Those with no response or progression or relapse within 6 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Finally, genetic studies in localized-stage FL may help better understand the clinical heterogeneity of FL, including patients with noted bad outcome, that is with early progression of disease and HT. 37,78,79 It is conceivable that localized-stage FL could have a better prognosis not only derived from the lower tumour burden and its curability, but by being particularly slow-growing (which, in turn, would aid in being diagnosed at a localized stage) or sensitive to therapy. In line with that possibility, in a series of stage II-IV ICT-treated patients with FL, none of the patients with stage II showed either HT or refractoriness to treatment 78 although this subgroup was small.…”
Section: Per S Pec Tive S For the Ne Ar Futu Rementioning
confidence: 99%
“…Finally, genetic studies in localized-stage FL may help better understand the clinical heterogeneity of FL, including patients with noted bad outcome, that is with early progression of disease and HT. 37,78,79 It is conceivable that localized-stage FL could have a better prognosis not only derived from the lower tumour burden and its curability, but by being particularly slow-growing (which, in turn, would aid in being diagnosed at a localized stage) or sensitive to therapy. In line with that possibility, in a series of stage II-IV ICT-treated patients with FL, none of the patients with stage II showed either HT or refractoriness to treatment 78 although this subgroup was small.…”
Section: Per S Pec Tive S For the Ne Ar Futu Rementioning
confidence: 99%
“…At present, it has become clear that FL is a very heterogeneous disease, and that the different prognostic subgroups can largely be drawn based on response to first-line immunochemotherapy (ICT). Thus, patients with poor response to frontline ICT have a poorer response to subsequent lines of therapy as well as a shorter overall survival (OS) [6][7][8], and they also seem to have notably higher rates of histological transformation (HT). Although it is unclear whether there is a late plateau in the HT curves [9]; HT is more frequent [7,8] and aggressive [10,11] shortly after diagnosis.…”
Section: Letter To the Editormentioning
confidence: 99%
“…Thus, patients with poor response to frontline ICT have a poorer response to subsequent lines of therapy as well as a shorter overall survival (OS) [6][7][8], and they also seem to have notably higher rates of histological transformation (HT). Although it is unclear whether there is a late plateau in the HT curves [9]; HT is more frequent [7,8] and aggressive [10,11] shortly after diagnosis. Conversely, patients with remission persisting 2 years after diagnosis (or perhaps as early as 1 year) can expect to live as long as the general population [12], which seems to indicate that their risk of death from either the disease or toxicity is lower.…”
Section: Letter To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Anti‐CD20 maintenance therapy prolongs remission and probably survival and has become a standard of care after first‐line therapy . Nevertheless, several studies have shown that approximately 15% to 20% of patients with FL will not respond to first‐line immunochemotherapy based on rituximab (refractoriness) or will experience early therapy failure (ETF), defined as relapse or progression within 2 years of commencing first‐line immunochemotherapy . The outcome for this subgroup of high‐risk FL patients is much worse than that of those who respond well to first‐line treatment, with reported 5‐year OS of approximately 50% versus 90% in the latter …”
Section: Introductionmentioning
confidence: 99%